Obstacles And Strategies For Purchasing In Procurement Of Quality Goods At Awann Sewu Boutique Hotel & Suite Semarang - Rizky Fitriana Ayuningtyas; Dedi Joko Purnomo (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Rizky Fitriana Ayuningtyas. C13.2019.00251, 2023. Obstacles and Strategies for Purchasing in Procurement of Quality Goods at Awann Sewu Boutique Hotel & Suite Semarang. Hospitality Management Applied Undergraduate Study Program, Faculty of Cultural Sciences, Dian Nuswantoro University.The Purchasing Section is part of the accounting department which is fully responsible for procuring goods as requested by the department, so that hotel operations run smoothly. This final project aims to describe the obstacles and find out the strategy of the purchasing department in the process of procuring goods at Awann Sewu Boutique Hotel & Suite. The author sees that there are obstacles faced by the purchasing department when the process of procuring goods at the hotel. Barriers are prone to occur both from the initial order until the goods have been sent which can affect hotel operations. besides that, the author also looks at the strategies implemented by the purchasing department to overcome obstacles. This study uses a qualitative descriptive method for the data collection process. The data obtained were collected by interview, observation and documentation techniques so as to obtain accurate data regarding the barriers and strategies of the purchasing department in procuring goods. The results of this study describe the obstacles in the Purchasing department in the process of procuring goods at Awann Sewu Boutique Hotel & Suite, so that the Purchasing department needs to implement a strategy in procuring goods to overcome the occurrence of obstacles.